2021
DOI: 10.1371/journal.ppat.1010033
|View full text |Cite
|
Sign up to set email alerts
|

The differentiation state of the Schwann cell progenitor drives phenotypic variation between two contagious cancers

Abstract: Contagious cancers are a rare pathogenic phenomenon in which cancer cells gain the ability to spread between genetically distinct hosts. Nine examples have been identified across marine bivalves, dogs and Tasmanian devils, but the Tasmanian devil is the only mammalian species known to have given rise to two distinct lineages of contagious cancer, termed Devil Facial Tumour 1 (DFT1) and 2 (DFT2). Remarkably, DFT1 and DFT2 arose independently from the same cell type, a Schwann cell, and while their ultra-structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…12: 220208 low CIITA-expressing cells. Alternatively, the inability to express MHC-II molecules in CIITA-overexpressing DFT2 cells might be due to epigenetic or post-transcriptional regulation, possibly as a consequence of the differentiation state of DFT2 tumours compared to DFT1 [29,57]. A heterozygous non-synonymous mutation (D59N) in transcription factor RFX5 was also described in DFT2 tumours [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12: 220208 low CIITA-expressing cells. Alternatively, the inability to express MHC-II molecules in CIITA-overexpressing DFT2 cells might be due to epigenetic or post-transcriptional regulation, possibly as a consequence of the differentiation state of DFT2 tumours compared to DFT1 [29,57]. A heterozygous non-synonymous mutation (D59N) in transcription factor RFX5 was also described in DFT2 tumours [6].…”
Section: Discussionmentioning
confidence: 99%
“…The lower expression of CIITA in CIITA-transfected DFT2 cells compared to CIITA-transfected DFT1 cells could be due to factors related to transgene copy number, genomic stability and integration sites, cellular metabolic state, or selection of low CIITA-expressing cells. Alternatively, the inability to express MHC-II molecules in CIITA-overexpressing DFT2 cells might be due to epigenetic or post-transcriptional regulation, possibly as a consequence of the differentiation state of DFT2 tumours compared to DFT1 [ 29 , 57 ]. A heterozygous non-synonymous mutation (D59N) in transcription factor RFX5 was also described in DFT2 tumours [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cellular origins of DFT1 and DFT2 could explain their different competitive capacities. DFT1 originated from a well‐differentiated myelinating Schwann cell (Owen et al., 2021 ) a cell type that usually exits the cell cycle and ceases growth (Tikoo et al., 2000 ; Yamauchi et al., 2004 ); however, DFT2 originated from a less differentiated immature or repair Schwann cell (Owen et al., 2021 ; Patchett et al., 2019 ), a cell type that retains the ability to proliferate (Tikoo et al., 2000 ; Yamauchi et al., 2004 ). Previous work (Patchett et al., 2019 ) found that, in comparison with DFT1, DFT2 transcriptomes were enriched in genes linked to cell migration consistent with a repair Schwann cell origin.…”
Section: Discussionmentioning
confidence: 99%
“…Visual examination of the DFT1 and DFT2 cells revealed morphological differences: DFT2 cells have a neuron-like phenotype, similar to their Schwann cell progenitor (Owen et al, 2021), while DFT1 cells have a rounder shape (Figure 1b,c). To test the hypothesis that DFT2 is a better competitor than DFT1, we first grew DFT1 and DFT2 cell lines in monoculture (Figure 2).…”
Section: Dft2 Shows a Higher Growth Rate But Lower Carrying Capacity ...mentioning
confidence: 99%